Do differences in initial speed persist to the stroke phase in front-crawl swimming? - Takeda, T.; Ichikawa, H.; Takagi, H.; Tsubakimoto, S. (Journal of Sports Sciences, 2009)
The purpose of the study was to determine the extent to which differences in initial speed persist to the stroke phase in front-crawl swimming. Ten male college swimmers performed trials for three types of start that produced different initial speeds: maximal-effort dive, submaximal-effort dive, and maximal-effort wall push. The submaximal effort was determined by the swimmer himself. Participants swam 25 m for each trial, and their motions were recorded by five fixed cameras positioned lateral to the direction of swimming. The horizontal velocity of the greater trochanter of the femur was used to define swimming speed. Mean swimming speed, evaluated from the initial-speed phase to the stroke phase, differed across trials. The effect sizes of the initial-speed phase were 3.15 between maximal-effort dive and submaximal-effort dive (P < 0.001), 5.00 between maximal-effort dive and maximal-effort wall push (P < 0.001), and 2.71 between submaximal-effort dive and maximal-effort wall push (P < 0.001). However, differences in speed at the stroke phase were small (maximal-effort dive: 1.91 ± 0.07 m/s; submaximal-effort dive: 1.88 ± 0.06 m/s; maximal-effort wall push: 1.88 ± 0.07 m/s), indicating that differences in initial speed do not persist to the stroke phase in front-crawl swimming.